Immunotherapy combinations for chronic lymphocytic leukemia: advantages and disadvantages. (2nd January 2023) - Robak, Pawel; Robak, Tadeusz
ABSTRACT: In the last few years, BTK inhibitors, PI3K inhibitors, and venetoclax have been approved for clinical use against chronic lymphocytic leukemia (CLL), both as single agents, and in combination. This article summarizes recent achievements in the treatment of patients with CLL, and pays special attention to novel targeted drugs and monoclonal antibodies (Mabs). A literature search was conducted of the PubMed and Google Scholar databases. Rituximab and obinutuzumab have been combined with chemotherapy, and more recently, with BTK inhibitors, PI3K inhibitors, and venetoclax. These agents have demonstrated high activity in treatment naïve (TN) and relapsed or refractory (RR) CLL. Immunochemotherapy regimens are currently considered in TN younger patients with IGHV -mutated disease and should not be given in patients without IGHV mutation. BTK inhibitors are more commonly used as monotherapy in TN and RR patients. PI3K inhibitors can be combined with CD20 Mabs, but their use in CLL is limited due to safety concerns. Venetoclax is typically combined with anti-CD20 Mabs in CLL. Generally, the optimal sequencing of therapies remains to be established, and the selection of upfront therapy needs to be tailored to the individual patient.